CELEBRATING GOD, HIS WORKS, AND HIS KINGDOM IN MY SONG: THEOLOGICAL SKETCHES IN THE ASAPH’S PSALMS THE BOOK III OF THE HEBREW PSALTER - Artur da Silva Ribeiro, Ailton (Práxis Teológica, 2022)
The Psalms are special compositions that express the history, the quotidian and the aspirations for the future of the God`s people, expressed by their musicians and gifted compositors. The way YHWH has acted in the past, the way He acts today and the hope the Psalmist expect from Him for the future, lead the compositions of these Psalms. In their poetic and melodic compositions, expressing about God`s personality, the Psalmists express their conceptions, fears and hopes. This research showed that the Psalmist Asaph talks about the theological and eschatological concepts related to the creator, redeemer, and maintainer God of the life. In Him was the hope rather of the Psalmist rather of the Israel people.